The relationship between first-year Nghe An College students' motivation to read and their use of reading strategies - Đào, Thị Minh Hương (University of Foreign Languages and International Studies, 2017)
The role of motivation in second language learning. Factors affecting students‟ motivation in the learning enviroment. The role of the teacher and the students in teaching and learning Reading. Key Features, Communicative Competence as the Major Goal and Greater Self-Direction for Readers.